2014
DOI: 10.1007/s00125-014-3185-0
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-specific deficiency of Janus kinase (JAK) 2 in mice impairs lipolysis and increases body weight, and leads to insulin resistance with ageing

Abstract: Our results suggest that adipocyte JAK2 plays a critical role in the regulation of adipocyte biology and whole-body metabolism. Targeting of the JAK-STAT pathway could be a novel therapeutic option for the treatment of obesity and type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 45 publications
6
52
1
Order By: Relevance
“…Indeed, consistent with impaired BAT function, our previous work showed extensive adipose expansion and the development of progressive obesity in A-Jak2 KO mice even on a chow diet [25]. At 1 month of age, when there was no difference in body weight, A-Jak2 KO mice had decreased BAT Ucp1 mRNA abundance that was associated with lower whole-body energy expenditure (Fig.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Indeed, consistent with impaired BAT function, our previous work showed extensive adipose expansion and the development of progressive obesity in A-Jak2 KO mice even on a chow diet [25]. At 1 month of age, when there was no difference in body weight, A-Jak2 KO mice had decreased BAT Ucp1 mRNA abundance that was associated with lower whole-body energy expenditure (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Of note, A-Jak2 KO mice were obese even when maintained at 20°C. This difference compared with Ucp1 −/− mice may be attributable to the suppression of lipolysis in white adipose tissue as a result of JAK2 deficiency, as we and others have previously shown [25,36]. In this work, we showed that JAK2 is required for full activation of the thermogenic response to a β 3 -adrenergic agonist, suggesting that JAK2 acts downstream of β-adrenergic signalling in adipocytes.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The precise cascade of events whereby GH stimulates adipose tissue lipolysis is incompletely understood, and there is a lack of human in vivo studies examining these events. Administration of GH to normal subjects increases STAT-5b phosphorylation and SOCS3 mRNA in adipose tissue (10) and a recent study in JAK2 knockout mice reported impaired lipolysis (18). The biological function of the SOCS/CISH proteins is mainly to feedback inhibit the JAK/STAT signaling pathway (1).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%